Polar auxin transport is implicated in vessel differentiation and spatial patterning during secondary growth in Populus. Issue 2 (8th March 2018) - Johnson, Dan; Eckart, Phoebe; Alsamadisi, Noah; Noble, Hilary; Martin, Celia; Spicer, Rachel
Abstract : Premise of the Study: Dimensions and spatial distribution of vessels are critically important features of woody stems, allowing for adaptation to different environments through their effects on hydraulic efficiency and vulnerability to embolism. Although our understanding of vessel development is poor, basipetal transport of auxin through the cambial zone may play an important role. Methods: Stems of Populus tremula × alba were treated with the auxin transport inhibitor N ‐1‐naphthylphthalamic acid (NPA) in a longitudinal strip along the length of the lower stem. Vessel lumen diameter, circularity, and length; xylem growth; tension wood area; and hydraulic conductivity before and after a high pressure flush were determined on both NPA‐treated and control plants. Key Results: NPA‐treated stems formed aberrant vessels that were short, small in diameter, highly clustered, and angular in cross section, whereas xylem formed on the untreated side of the stem contained typical vessels that were similar to those of controls. NPA‐treated stems had reduced specific conductivity relative to controls, but this difference was eliminated by the high‐pressure flush. The control treatment (lanolin + dimethyl sulfoxide) reduced xylem growth and increased tension wood formation, but never produced the aberrant vessel patterning seen in NPA‐treated stems. Conclusions: These results are consistent with a model of vessel development in which basipetal polar auxin transport through the xylem‐side cambial derivatives is required for proper expansion and patterning of vessels and demonstrate that reduced auxin transport can produce stems with altered stem hydraulic properties.